UniKL Business School: The Opportunities Towards Becoming A Preferred University - Arman Hj Ahmad; Professor Dr Wan Sabri Wan Hussin (International Journal of Technology and Education Research, 2023)
Becoming the first and ultimate preferred institution for pursuing higher degree or tertiary education in Malaysia became an ultimate dream of every university or higher learning institution of this country. This paper focuses on some higher learning opportunities need to be highlighted by Universiti Kuala Lumpur Business School’s management in order to become the preferred university among Malaysian simultaneously be the best in the country. In this competitive environment, be the best is crucial. Thus, one of the ways of becoming the best is by grabbing as much as opportunities that lie in the market. There are several opportunities found important for UniKL Business School and those are the new target market opportunities (working adult), modular learning due to strategic location and high number of target market, recognition for the current degree program by professional bodies, professional certificate embedded the current degree program (added value) and becoming an accredited learning center for professional course. Careful analyses of eighteen articles with different themes on business opportunities in higher learning institution yield some insights on issues prevalent in the matter. Finally, this paper proposes an integrated model for the suggestions on how UniKL Business School could grab those opportunities (creating, shaping, recognizing and seizing). The model is constructed based on insights drawn from the analyses of the articles. The model may be used as a guide for UniKL Business School and may be useful tools for consultants to use in handling tasks relating to the developing of the preferred higher learning institution in Malaysia